PEA YIELD DEPENDING ON SOWING RATES IN THE CONDITIONS OF THE WESTERN FOREST-STEPPE OF UKRAINE - Lykhochvor В.; Andrushko М.; Andrushko О. (Bulletin of Lviv National Environmental University. Series Agronomy, 2025)
During 2022–2024, field studies were carried out at the experimental site of Lviv National Environmental University to determine the optimal sowing rate for the Salamanca pea variety under conditions of sufficient moisture in the Western Forest-Steppe region. The soil at the experimental plot is classified as dark gray podzolized, with a humus content of 2.2%. The accounting area measures 50 m², and the experiments were repeated three times. The layout of the plots was systematic, with sowing rates evaluated in the range of 0,9; 1,0; 1,1; 1,2; 1,3; 1,4 million seeds per hectare. The peas were cultivated using intensive agricultural practices, ensuring adherence to all technological components. The preceding crop for the peas was winter wheat. The fertilization regimen included Р60К60 + N60 + Mg20 + S30 + Intermag legumes (2 l/ha). Nitrogen fertilizers (ammonium nitrate, N34) were applied for straw mineralization following the wheat harvest, before disking. In the fall, triple superphosphate (Р46), potassium chloride (К60), and sulfur fertilizers (Vigor, S90) were applied during plowing. Magnesium (magnesium sulfate, S30Mg20) was introduced in the spring as part of the pre-sowing soil cultivation. Additionally, Intermag legumes microfertilizer was applied at the onset of the pea budding phase, concurrently with the fungicide Fox. Sowing occurred from April 1 to 3, with the seeding rates adhering to the experimental design and a sowing depth of 5 cm. It was found that the highest yield (5.60 t/ha) of Salamanca variety grain on average over three years of research was formed at a seeding rate of 1.0 million/ha. It also remained high at a seeding rate of 0.9 million/ha – 5.54 t/ha. Thickening of pea crops led to a decrease in grain yield. Thus, at a seeding rate of 1.1 million/ha it was 5.48 t/ha, which is 0.12 t/ha less than the seeding rate of 1.0 million/ha. At a seeding rate of 1.2 million/ha, there was a further decrease in yield to 5.38 t/ha. Increasing the seeding rate to 1.3 million/ha resulted in a yield of 5.29 t/ha, which is 0.31 t/ha lower than the most productive option. Increasing of the seeding rate to 1.4 million/ha caused a decrease of yield to 5.15 t/ha, which is 0.45 t/ha less than the rate of 1.0 million/ha. According to the research results, the highest grain yield of peas (5.76 t/ha) was obtained in 2024. In 2023, the yield was slightly lower – 5.56 t/ha, and the lowest was in the first year of research – 4.90 t/ha. Under the influence of hydrothermal conditions of the year, the yield of peas varied in a wider range (0.86 t/ha) than under the influence of the seeding rate (0.45 t/ha).